Study of Amino Acids and Carbohydrates from The Leaves of Ehretia laevis - C. Torane, Rasika; D. Ruikar, Anjali; S. Chandrachood, Pranav; R. Deshpande, Nirmala (Asian Journal of Chemistry, 2010)
An Indian traditional medicinal plant, Ehretia laevis Roxb. commonly called Bhokara belongs to family Boraginaceae. All parts of the plant are medicinally important. They are used in dropsy, anasaraca, urticaria, cholera, dysentery, etc. Detection of amino acids from two different extracts was carried out using paper chromatographic technique. Both extracts showed presence of different amino acids. These were compared with the standards. Presence of carbohydrates was performed using paper chromatographic techniques and compared with the standards.